Understanding Self-Gift Consumer Behaviour in Negative Contexts in China: The Influences of Chinese interdependent notion of the self on therapeutic SGCB - Weng, Meilin (2010)
While evidence of the significance of Self-Gift Consumer Behaviour (SGCB) in Western cultures has been shown in the prior research, particularly in the United States, there is little understanding of this behaviour in collectivist cultures. Given its self-driven nature, further investigations on SGCB have been called for to address the possible cultural differences in Confucian societies. This paper responses to calls, and seeks to theoretically contribute to the field of consumer behaviour from a global perspective and from the point of view of consumers, by offering a Confucian conceptualization of SGCB. 14 in-depth interviews with Chinese consumers through online video calls are employed to affirm the existence of SGCB in China, and further to gain an insight into motivations for and emotions related to SGCB, with a particular focus on negative contexts. Findings show that Chinese people with interdependent selves use therapeutic SGCB as a way of caring oneself, pretending to be strong to preserve face, or asserting one’s identity in negative contexts. The therapeutic roles of SGCB to relieve stress and escape from certain feelings are also supported by the interview findings. Besides, emotions mediate the effects of the antecedents of SGCB and of the therapeutic nature of SGCB. The researcher suggests that the meaning of this distinct form of consumer behaviour in Confucian societies should be reflected by academics.